Dissection of the genetic architecture of peduncle vascular bundle‐related traits in maize by a genome‐wide association study. Issue 6 (9th February 2022) - Sun, Gaoyang; Zhang, Xuehai; Duan, Haiyang; Gao, Jionghao; Li, Na; Su, Pingping; Xie, Huiling; Li, Weihua; Fu, Zhiyuan; Huang, Yubi; Tang, Jihua
Summary: The peduncle vascular system of maize is critical for the transport of photosynthetic products, nutrients, and water from the roots and leaves to the ear. Accordingly, it positively affects the grain yield. However, the genetic basis of peduncle vascular bundle (PVB)‐related traits in maize remains unknown. Thus, 15 PVB‐related traits of 386 maize inbred lines were investigated at three locations (Yongcheng, 17YC; Kaifeng, 20KF; and Yuanyang, 20YY). The repeatability for the 15 traits ranged from 35.53% to 92.13%. A genome‐wide association study was performed and 69 non‐redundant quantitative trait loci (QTL) were detected, including 9, 41, and 27 QTL identified at 17YC, 20KF, and 20YY, respectively. These QTL jointly explained 4.72% (SLL) to 37.30% (NSVB) of the phenotypic variation. Eight QTL were associated with the same trait at two locations. Furthermore, four pleiotropic QTL were identified. Moreover, one QTL ( qPVB44 ), associated with NSVB_20KF, was co‐localized with a previously reported locus related to kernel width, implying qPVB44 may affect the kernel width by modulating the number of small vascular bundles. Examinations of the 69 QTL identified 348 candidate genes that were classified in five groups. Additionally, 26 known VB‐related homologous genes (e.g. VLN2, KNOX1, and UGT72B3 ) were detected in 20 of the 69 QTL. A comparison of the NSVB between a Zmvln2 EMS mutant and its wild type elucidated the function of the candidate gene ZmVLN2 . These results are important for clarifying the genetic basis of PVB‐related traits and may be useful for breeding new high‐yielding maize cultivars.